SOM PROBLEMSOF COMPILING THE DICTIONARY OF LEGAL TERMS - Aymbetov , Мәди Айтбенбетұлы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2018)
Article еxaminessom of the linguistic problems of compiling the dictionary of legal terms.